92.3k views
1 vote
2•7x • (2x+ 5x) - 36x + 3x

2 Answers

2 votes

Answer and Step-by-step explanation:


\huge\boxed{~~Answer:98x^2-33x~~}

Let's simplify the equation step-by-step:


=(2)(7)x(2x+5x)-36x+3x


=98x^2+-36x+3x

Now, combine Like Terms:


=98x^2+-36x+3x


=(98x^2)+(-36x+3x)


=98x^2+-33x

User Knut Eldhuset
by
5.3k points
3 votes

Answer:

65x

Explanation:

14x(7x)-36x+3x

98x-36x+3x=65x

User Scoopzilla
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.